First Ionospheric Results From the MAVEN Radio Occultation Science Experiment (ROSE). Issue 5 (18th May 2018) - Withers, Paul; Felici, M.; Mendillo, M.; Moore, L.; Narvaez, C.; Vogt, M. F.; Jakosky, B. M.
Abstract: Radio occultation observations of the ionosphere of Mars can span the full vertical extent of the ionosphere, in contrast to in situ measurements that rarely sample the main region of the ionosphere. However, most existing radio occultation electron density profiles from Mars were acquired without clear context for the solar forcing or magnetospheric conditions, which presents challenges for the interpretation of these profiles. Here we present 48 ionospheric electron density profiles acquired by the Mars Atmosphere and Volatile EvolutioN mission (MAVEN) Radio Occultation Science Experiment (ROSE) from 5 July 2016 to 27 June 2017 at solar zenith angles of 54° to 101°. Latitude coverage is excellent, and comprehensive context for the interpretation of these profiles is provided by other MAVEN instruments. The profiles show a 9‐km increase in ionospheric peak altitude in January 2017 that is associated with a lower atmospheric dust storm, variations in electron densities in the M1 layer that cannot be explained by variations in the solar soft X‐ray flux, and topside electron densities that are larger in strongly magnetized regions than in weakly magnetized regions. MAVEN Radio Occultation Science Experiment electron density profiles are publicly available on the NASA Planetary Data System. Key Points: MAVEN now performs radio occultation observations Derived profiles consistent with previous experiments Observe full ionospheric profile with comprehensive MAVEN context